(untitled) (Research, Society and Development, 2022)
This work demonstrates the main elements of the risk management system at a Brazilian umbilical cord blood bank, taking into account the criticality and individuality of the procedures as well as regulatory and certifying agency guidelines. This study involved the implementation of a Risk Management Committee which was responsible for process flow mapping; identifying, analyzing, classifying, treating, and monitoring risks using brainstorming, flowcharts, Pareto distribution, Ishikawa diagrams, and FMEA. Almost 900 risks were divided into 16 sectors, with 24% of total risks in the Blood Processing sector, demonstrating a strong relationship between critical activities and exposure to risks. Occurrence and severity were defined, followed by risk treatment and monitoring. The risk management system provided a more reliable infrastructure to customers and employees, upgraded the capabilities of the company, successful ISO 9001: 2015 certification, and renew American Association of Blood Bank accreditation. This paper presents a specific look at the implementation of a risk management system in a private umbilical cord blood bank. Typically, this sort of information is kept in internal company documents and is not widely disclosed in the literature. In this sense, this study presents a useful perspective for practitioners and academics.